Differences in hospital- and ventilator-associated pneumonia due to Staphylococcus aureus (methicillin-susceptible and methicillin-resistant) between Europe and Latin America: A comparison of the EUVAP and LATINVAP study cohorts (2012)
Purpose: A comparison is made of epidemiological variables (demographic and clinical characteristics) and outcomes in patients with hospital-acquired pneumonia (HAP) or ventilatorassociated pneumonia (VAP) caused by methicillin-susceptible and methicillin-resistant Staphylococcus aureus (MSSA and MRSA) in the Latin American VAP (LATINVAP) vs. the European Union VAP (EUVAP) cohorts of patients admitted to intensive care units (ICUs). Methods: The EUVAP project was a prospective, multicenter observational study reporting 827 patients with HAP/VAP in 27 ICUs from 9 European countries. The LATINVAP project was a multicenter prospective observational study, with an identical design, performed in 17 ICUs from 4 Latin American countries involving 99 patients who developed HAP/VAP. Episodes of VAP/HAP caused by S. aureus, MSSA, and MRSA were compared in both cohorts. Results: Forty-five patients had S. aureus HAP/VAP in the EUVAP cohort vs. 11 patients in the LATINVAP cohort. More patients had MRSA in the LATINVAP study than in the EUVAP (45% vs. 33%). ICU mortality among patients with MSSA HAP/VAP in EUVAP was 10% vs. 50% for LATINVAP (OR = 9.75, p = 0.01). Fifteen patients in the EUVAP cohort developed MRSA HAP/VAP as opposed to 5 in LATINVAP. In the EUVAP study there was an ICU mortality rate of 33.3%. In the LATINVAP cohort, the ICU mortality rate was 60% (OR for death = 3.0; 95%CI 0.24---44.7). Conclusion:MRSApneumoniawasassociatedwithpooreroutcomesincomparisonwithMSSA.OurstudysuggestssignificantvariabilityamongEuropeanandLatinAmericanICUpracticesthatmayinfluenceclinicaloutcomes.Furthermore,patientswithpneumoniainLatinAmericahavedifferentoutcomes.